A history of market performance
1 online resource (xxii, 590 pages)
Keywords: "This exciting new volume examines the development of market performance from Antiquity until the dawn of the Industrial Revolution. Efficient market structures are agreed by most economists to serve as evidence of economic prosperity, and to be prerequisites for further economic growth. However, this is the first study to examine market performance as a whole, over such a large time period. Presenting a hitherto unknown and inaccessible corpus of data from ancient Babylonia, this international set of contributors are for the first time able to offer an in-depth study of market performance over a period of 2,500 years. The contributions focus on the market of staple crops, as they were crucial goods in these societies. Over this entire period, all papers provide a similar conceptual and methodological framework resting on a common definition of market performance combined with qualitative and quantitative analyses resting on new and improved price data. In this way, the book is able to combine analysis of the Babylonian period with similar work on the Roman, Early-and Late Medieval and Early Modern period. Bringing together input from assyriologists, ancient historians, economic historians and economists, this volume will be crucial reading for all those with an interest in ancient history, economic history and economics"--